2016
DOI: 10.4236/ojn.2016.67054
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aroma Hand Massage on Fatigue and Sleeping among Hospice Patients

Abstract: Purpose: The purpose of this study was the comparative effects on fatigue and sleep of aroma hand massage vs. hand massage among hospice patients in a hospital. Methods: The design of this study was a nonequivalent comparison group pretest-posttest design. This study was performed from May to December 2012 in a hospice ward. A total of 30 hospice patients in a hospice ward participated in the study (17 in an aroma massage group and 13 in a massage group). The Piper Fatigue Scale was used to measure the fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Based on the results, fatigue decreased in both groups of the aromatherapy intervention, but the aromatherapy by massage was more effective in reducing the fatigue of these patients. A study on assessing the effect of aromatherapy by hand massage on fatigue and sleep among North Korean hospital patients, showed that aromatherapy by massage is effective in reducing fatigue and improving the quality and quantity of sleeping (Park, Chun, & Kwak 2016), which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the results, fatigue decreased in both groups of the aromatherapy intervention, but the aromatherapy by massage was more effective in reducing the fatigue of these patients. A study on assessing the effect of aromatherapy by hand massage on fatigue and sleep among North Korean hospital patients, showed that aromatherapy by massage is effective in reducing fatigue and improving the quality and quantity of sleeping (Park, Chun, & Kwak 2016), which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Orange contains linalool, linalyl acetate and limonene. Similar to lavender oil, it has a sedative and anti-anxiety effect and helps maintain homeostasis and reduce mental stress (Park et al, 2016;Watanabe et al, 2015). Rosemary affects the gastrointestinal and cardiovascular system by relieving constipation and colic pain and regulating blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A surprisingly limited body of evidence was found on the impact of olfactory stimulation on physical functioning, such as sleep, food intake and balance. This is despite literature stating that smell cues can modify eating behaviours ( Zoon et al, 2016 ), enhance sleep pattern ( Park et al., 2016 ) and improve postural control ( Freeman et al, 2009 ). Although limited, the current review provides evidence of the benefit on the total and sustained hours slept of people with dementia following overnight odour exposure for 3–4 weeks.…”
Section: Discussionmentioning
confidence: 96%